Fonio and Bambara Groundnut value chains in Mali: issues, needs, and opportunities for their sustainable promotion - Mbosso, Charlie; Boulay, Basile; Padulosi, Stefano; Meldrum, Gennifer; Mohamadou, Youssoufa; Berthe Niang, Aminata; Coulibaly, Harouna; Koreissi, Yara; Sidibé, Amadou (MDPI, 2020)
As the effects of climate change are severely straining West African agricultural systems, the adoption of more incisive interventions in support of sustainable development agendas for the region is highly critical and cannot be further delayed by governments. Neglected and underutilized species (NUS) are one important ally in pursuing resilience in both production and food systems because of their promising traits in terms of nutrition, adaptation to local agroecosystems, and economic potential for local populations. Focusing on fonio, a gluten-free traditional cereal, and Bambara groundnut, a protein-rich leguminous crop, we investigate issues in their production, commercialization, and consumption in southern Mali. The aim was to assess needs and opportunities for improving their value chains and increasing their use and societal benefits. Using a Rapid Market Appraisal method, we surveyed traders, producers, processors, and consumers of target crops in 2017 and 2018. Our findings indicate that while both crops are consumed and praised by local populations, critical bottlenecks inhibit their wider socioeconomic potential. Lack of access to inputs and equipment and presence of sand in the commercialized product are important issues for fonio, whereas the Bambara groundnut value chain suffers from poor processing facilities and lack of market promotion. Policy recommendations to tackle the identified bottlenecks are proposed.